2021
DOI: 10.3390/app11052129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Veneering Ceramic and Methods on Failure Load of Veneered Zirconia

Abstract: Background: A variety of veneering options to zirconia frameworks are now available. The purpose of this study is to evaluate the effect of veneer materials, veneering methods, cement materials, and aging on the failure load of bilayered veneer zirconia. Material and methods: Zirconia bars (20 × 4 × 1 mm) were veneered to 2 mm total thickness (n = 10/group). Veneering method groups included: 1. Hand-layered feldsparthic porcelain (VM = Vita VM9, Vident) and fluorapatite glass–ceramic (CR = IPS e.max Ceram, Ivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[10] reported that 0.8% of 264 single crowns and 0.8% of 120 partial fixed dental prostheses (FDPs) experienced chipping of the veneering ceramic within the 1st year. Other research groups observed even higher percentages after 3 and 5 years (13.0% and 15.2%, respectively) [9]. Although there are numerous zirconia materials and milling machines available, as well as extensive research has been undertaken on surface modification techniques, such as bonding‐agent chemical deposition, silica coating, etching, mechanical grinding, and blasting, the secure achievement of adequate bond strength between zirconia substrate and the veneer remains a significant concern for the long‐term viability of zirconia restorations in the oral cavity [11].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[10] reported that 0.8% of 264 single crowns and 0.8% of 120 partial fixed dental prostheses (FDPs) experienced chipping of the veneering ceramic within the 1st year. Other research groups observed even higher percentages after 3 and 5 years (13.0% and 15.2%, respectively) [9]. Although there are numerous zirconia materials and milling machines available, as well as extensive research has been undertaken on surface modification techniques, such as bonding‐agent chemical deposition, silica coating, etching, mechanical grinding, and blasting, the secure achievement of adequate bond strength between zirconia substrate and the veneer remains a significant concern for the long‐term viability of zirconia restorations in the oral cavity [11].…”
Section: Introductionmentioning
confidence: 90%
“…However, the fact that the veneering material is weaker than the substrate may lead to failure, because of crack propagation under low loads and tension [7]. Crack propagation can originate from the substrate/veneer interface, the veneer surface, or the inner surface of the substructure [8,9]. This type of failure, known as ceramic chipping or delamination of the veneering ceramic, is commonly observed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the strong occlusal forces acting in the posterior areas, cohesive fractures of veneering ceramics occur more frequently than failures of zirconia infrastructures, which have demonstrated excellent fracture resistance [16]. Consequently, the use of monolithic zirconia restorations has become an attractive alternative due to improved aesthetic appearance, good mechanical behavior, a simplified technological process, and the advantage of a more conservative tooth preparation [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%